Yoga Exercises in Reduce Homa-Ir and Insulin Levels in Polycystic Ovarium Syndrome (PCOS) Insulin Resistant - Zakkiyatus Zainiyah; Muhammad Suhron (Journal Of Nursing Practice, 2023)
Background: Polycystic Ovary Syndrome (PCOS), an endocrine disease that causes infertility in reproductive women, characterized by hyperandrogenemia, chronic anovulation, and Polycystic Ovary Morphology (PCOM), most PCOS women have metabolic disorders. The HOMA-IR can be used as a clinical index that is easy and sensitive to assess ovarian function in insulin-resistant PCOS women. The HOMA-IR examination has never been performed on obese PCOS patients in Madurese and Indonesia, it was carried out in Madura because it has the potential for obesity with unfavorable lifestyles such as consuming high carbohydrates and a tendency to obesity in PCOS patients. Purpose: The aim of this study was to analyze yoga exercises in reducing HOMA-IR and Insulin Levels in insulin-resistant polycystic ovary syndrome (PCOS) in the Madurese. Methods: Analytic observational study with a case-control study design, a sample of 50 patients (cases of PCOS) and 50 healthy women (non-PCOS) in the Madurese tribe, serum was taken to check HOMA-IR and insulin levels, which were examined in the laboratory. Chi-square statistical test with significance 0.05. Results: The results Chi-square statistical test with significance 0.05 showed that the case group before being given Yoga exercises the average HOMA-IR results were 40.97 and insulin levels were 61.38?l/ml while in the control group the average HOMA-IR results were 1.54 and average insulin levels were 2.9-21?l /ml, after doing Yoga exercises for 12 times and 2 times a week. Conclusion: There is a decrease in the HOMA-IR value and insulin levels. The HOMA-IR values and insulin levels decreased between before and after being given gymnastics in the case group.